AI-Integrated Smart Glasses for Enhancing Reading and Guidance Independence for the Visually Impaired - J., Rajichellam; Kumar, Baskaruni Dinesh Balaji; Sai, Bommannagari Usha; Karthik, Sangaraju Siva (Journal of Trends in Computer Science and Smart Technology, 2024)
Since there are blind and partially sighted people all over the world, they face significant challenges when it comes to reading. In the past, Braille was the only solution for the blind and visually impaired to read and learn. However, there is a lack of training in Braille and a shortage of Braille machines and facilities. To address these issues, a smart reader for the blind integrated with Raspberry Pi technology has been proposed. The system utilizes YOLO (You only look once) for object detection, OCR (Optical Character Reader) for text recognition, and Google Text-to-Speech to capture and read text aloud through a speaker or headphone. Smart glasses offer real-time assistance and enhance the daily lives of visually impaired individuals. Through a combination of sensors, cameras, and audio feedback systems, these smart glasses enhance the reading capability of the visual impaired. Moreover, advancements in artificial intelligence and Deep learning algorithms further enhance the capabilities of these devices, enabling more accurate personalized assistance.